Design Science Research : A Method for Science and Technology Advancement - Dresch, Aline; Lacerda, Daniel Pacheco; Antunes Jr, José Antônio Valle (Springer International Publishing : Imprint: Springer, 2015)
Consolidating existing knowledge in Design Science, this book proposes a new research method to aid the exploration of design and problem solving within business, science and technology. It seeks to overcome a dichotomy that exists in the field between theory and practice to enable researches to find solutions to problems, rather than focusing on the explanation and exploration of the problems themselves.   Currently, researches concentrate on to describing, exploring, explaining and predicting phenomena, and little attention is devoted to prescribing solutions. Herbert Simon proposes the need to develop a Science of the Artificial (Design Science), arguing that our reality is much more artificial than natural. However, the research conducted on the Design Science premises has so far been scattered and erratic in different fields of research, such as management, systems information and engineering. This book aims to address this issue by bringing these fields together and emphasising the need for solutions.   This book provides a valuable resource to students and researchers of research methods, information systems, management and management science, and production and operations management.   .